2002
DOI: 10.1162/089892902317361895
|View full text |Cite
|
Sign up to set email alerts
|

GABA-ergic Modulation of Prefrontal Spatio-temporal Activation Pattern during Emotional Processing: A Combined fMRI/MEG Study with Placebo and Lorazepam

Abstract: Various prefrontal cortical regions have been shown to be activated during emotional stimulation, whereas neurochemical mechanisms underlying emotional processing in the prefrontal cortex remain unclear. We therefore investigated the influence of the GABA-A potentiator lorazepam on prefrontal cortical emotional-motor spatio-temporal activation pattern in a combined functional magnetic resonance imaging/magnetoencephalography study. Lorazepam led to the reversal in orbito-frontal activation pattern, a shift of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 78 publications
(120 reference statements)
6
28
0
2
Order By: Relevance
“…Deakin et al (2004) demonstrated that compared to a placebo group, 20 mg diazepam produced an increase in the amount wagered on the riskiest trial type (e.g., lower chance to win, but higher payoff, thus having the greatest risk/benefit conflict). Northoff et al (2002) showed that administration of lorazepam modulated activity in the orbitofrontal cortex during processing of negative emotional stimuli. Several studies have shown alcohol-induced changes in risky decision making (George et al 2005;Lane et al 2004;Roehrs et al 2004;Stoner et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Deakin et al (2004) demonstrated that compared to a placebo group, 20 mg diazepam produced an increase in the amount wagered on the riskiest trial type (e.g., lower chance to win, but higher payoff, thus having the greatest risk/benefit conflict). Northoff et al (2002) showed that administration of lorazepam modulated activity in the orbitofrontal cortex during processing of negative emotional stimuli. Several studies have shown alcohol-induced changes in risky decision making (George et al 2005;Lane et al 2004;Roehrs et al 2004;Stoner et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Neural correlates and functional mechanisms underlying these interactions remain unclear. Lesion and functional imaging studies have predominantly related emotional processing to medial prefrontal cortical regions, such as the ventro-and dorsomedial prefrontal cortex (VMPFC, DMPFC) as well as the medial orbitofrontal cortex (MOFC) [Damasio, 1999;Davidson and Irwin, 1999;Northoff et al, 2000Northoff et al, , 2002Phan et al, 2002]. In contrast, cognitive tasks have been implicated in the activation of lateral prefrontal cortical regions, such as the ventro-and dorsolateral prefrontal cortex (VLPFC, DLPFC) and adjacent lateral prefrontal cortical regions [see Duncan and Owen, 2000 for an overview].…”
Section: Introductionmentioning
confidence: 99%
“…Finally neurochemical challenge studies during emotional stimulation, for example with lorazepam that relieves the acute catatonic state [61, 62], might also be of interest. This is especially so given the fact that lorazepam in healthy subjects modulates neural activity in those regions (the orbitofontal cortex) [74] that are altered in catatonia.…”
Section: How Can We Investigate the Neuronal Processes Of Defense Mecmentioning
confidence: 99%
“…In other studies right hemispheric dysfunction in the lateral parietal cortex was observed to correlate with spatial deficits [105]. The exact relationship between the midline and the right lateral parietal cortical changes, however, remains unclear [74.] What is ultimately needed are studies that link the different subjective experiences and their different individual contents in catatonic and hysterical conversion to different though probably overlapping neural networks with specific patterns of increased and decreased functional connectivity.…”
mentioning
confidence: 99%